AN ANALYSIS OF THE FOURTH SEMESTER STUDENTS’ COMPETENCES IN USING ELLIPTICAL CONSTRUCTION AT ENGLISH DEPARTMENT MUHAMMADIYAH UNIVERSITY OF NORTH MALUKU - Adi F. Mahmud; Aprianty Sibela (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Ilmu Pendidikan Universitas Muhammadiyah Maluku Utara, 2021)
Elliptical construction usually applies namely in spoken and written form. Elliptical construction is combination from two sentences, with different subject but have the same verb complement. And the elliptical construction or arrangement of sentence used to avoid unnecessary repetition of words in a sentence. This research aimed to know the extent of students’ competence in using elliptical construction to the fourth semester students at English Department of Muhammadiyah University. This research used descriptive qualitative. The subjects of this study were the fourth semester students of the English Department, they consisted of 20 respondents. The data were collected through test items, the data were analyzed by using tabulated into rating scale and qualification. This research found out that only 2 respondents had very good category with the score 90-93, there were 3 respondents had good category with the score 80, there were 4 respondents had sufficient category with the score 60-70, there were 5 respondents had poor category with the score 40-50 and 6 respondents got very poor category with the score 0-30. The students’ mastery use elliptical construction to complete the sentences categorized poor. This proven by the evidence total presentation students’ ability in doing the test of elliptical construction is 49, 9 %. Keywords— Key words: Students, Competence, Elliptical Construction